The challenges with Glässer’s disease in technified pig production - Pereira, Daniele A; Dalla Costa, Filipe A; Ferroni, Lívia B; Moraese, Carolina N; Schocken-Iturrino, Ruben P; Oliveira, Luís G (Austral Journal of Veterinary Sciences, 2017)
ABSTRACT. The swine upper respiratory tract is early colonised by Haemophilus parasuis, a bacteria which causes Glässer´s disease under favorable conditions. Glässer’s disease is a septicemic infectious disease characterised by causing polyserositis. The prevention of Glässer disease still represents a big challenge for the production chain, since the mechanism of systemic infection in pigs and virulence factors that prevent phagocytosis are not yet well understood. Even in swine herds with high sanitary standard, it is the main cause of mortality that has led to productive and economic losses in the pig industry worldwide. Although the H. parasuis genome sequence has been completed already, diagnosis is still difficult due to the existence of non-virulent strains and the early colonisation of the upper respiratory tract of healthy swines. This review aims to provide up-to-date information about the etiology, epidemiology, pathogenesis, clinical signs, gross and microscopic lesions, diagnosis, treatment and control of Glässer’s disease.